Sistem Perpustakaan Buku Digital Berbasis Website dan Aplikasi Telegram Menggunakan QR Code - Larissa Navia Rani; Dicky Wiransyah; Halifia Hendri (Jurnal KomtekInfo, 2022)
In general, information and communication technology or ICT (Information and Communication Technology) has become an inseparable part of global life. In the global era, the website aims to convey information digitally, such as the creation of a digital book library website for the need for information technology in disseminating information. The main problem faced by the Indonesian people, especially in the field of education during the COVID-19 pandemic, is the low level of quality of human resources. One of the efforts to improve the quality of resources for children, millennials, and even adults is the development of interest in reading books and the habit of reading books. The library is expected to be a center for the development of interest in reading books and the habit of reading books. During the COVID-19 pandemic, of course, libraries will be closed to prevent crowds and prevent the spread of COVID-19. Based on this problem, interest in reading books is getting lower, and to find books on the internet, on average, they are paid and difficult to access. To overcome these problems, new innovations and developments are needed from classic libraries to digital libraries by collaborating with computerized technology and information technology so that the resulting information can be presented quickly, precisely, efficiently and free of charge.